Non-sustained ventricular tachycardia on remote patient monitoring in heart failure patients. (14th October 2021) - Barradas Da Silva, M; Duarte, F; Oliveira, L; Serena, C; Fontes, A; Monteiro, A; Machado, C; Dourado, R; Santos, E; Pelicano, N; Pacheco, M; Tavares, A; et al.
Abstract: Background: Non-sustained ventricular tachycardia (NSVT) is commonly found in patients with structural heart disease and was historically obtained from registers of external ambulatory monitoring. The advent of remote patient monitoring (RPM) in Cardiac implantable electronic devices (CIEDs) has made it possible to detect asymptomatic NSVT in Heart Failure (HF) patients more frequently, but its impact in real world is uncertain. Purpose: To determine the clinical impact of NSVT detection in RPM in ischemic and non-ischemic chronic heart failure patients with reduced ejection fraction (HFrEF) and CIEDs. Methods: We retrospectively enrolled 121 consecutive patients with HFrEF, CIEDs and RPM. Patients were evaluated through routine episodic CIEDs interrogation, routine clinical evaluations and continuous monitoring data obtained from CIEDs and transmitted remotely to the care team and divided into NSVT positive (Group 1) and negative groups (Group 2). Primary endpoint was admissions to the emergency department by HF decompensation and secondary endpoint was the occurrence of arrhythmic events. A sub-analysis of non-ischemic HF was also performed. Results: NSVT was detected in 78 (72, 2%) patients. The mean number of episodes of NSVT was 611, 68±3271, 25 during the follow-up period or 2, 445±16, 688 in 24 hours. Mean age was 62, 40±13, 218 years, 71, 9% were males and mean follow-up period was 56, 30±39, 37 months. Fifty-eight patients (47, 9%) had transvenous implantable cardioverter defibrillator (ICD), 48 (39, 7%) implantable cardiac resynchronization therapy (CRT) defibrillator (CRT-D), 14 (11, 6%) subcutaneous ICD (S-ICD) and 1 (0, 8%) CRT pacemaker (CRT-P). Medium left ventricular ejection fraction (LVEF) was 34, 70±12, 53%, 25 (23, 14%) were in NYHA III-IV and 46 (39, 0%) were ischemic (29 (37, 7%) in Group 1 and 11 (37, 9%) in Group 2). NSVT was associated with the occurrence of sustained ventricular tachycardia (VT) (1, 88±0, 186episodes of VT in group 1 and 0, 03±0, 186 in group 2, p=0, 012), ventricular fibrillation (VF) (1, 44±5, 325 episodes of VT in group 1 and 0, 03±0, 186 in group 2, p=0, 011) and admissions to the emergency department by HF decompensation at 5 years (r=0, 310, p=0, 011). A sub-analysis in non-ischemic HF patients also showed correlation between NSVT and VT (r=0, 602, p<0, 05) and admissions to the emergency department by HF decompensation at 5 years (r=0, 382, p=0, 014). Conclusions: On remote patient monitoring with CIEDs, NSVT in HF patients was associated with arrhythmic events and may serve as a predictor for HF decompensations. Funding Acknowledgement: Type of funding sources: None.